The level of psychological resilience among mothers of children with mental handicap (A field study in Lattakia city) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the research was to identify the level of psychological resilience among mothers of children with mental handicap, to identify the differences in their psychological resilience according to the mother's educational level and the severity of the child's disability. The researcher adopted the descriptive approach and used the psychological resilience scale of Connor and Davidson (2003) which translated and standardized in the Syrian environment by Alasmi (2012). The research sample consisted of (40) mothers of children with mental disabilities who visit the Women's Support and Empowerment Center in Lattakia in a simple random manner. The results showed that the largest percentage of mothers(57.5%) have a low level between (17-40) of psychological resilience, there are no differences in psychological resilience among mothers according to the mother's educational level, while there are differences according to the severity of the child's mental disability in favor of the highest severity of disability.